Decreased Plaque Score Due to Gargling with Guava Leaf Decoction Among Adolescents at the “Sejati Muhammadiyah Rappang” Social Welfare Institution Sidenreng Rappang Regency - Juwita Husaini; Rosmawaty; Muhammad Tahir; Ayu Lestari (Universitas STRADA Indonesia, 2024)
Plaque plays an important role in the occurrence of dental and oral diseases such as dental caries and periodontal disease. Plaque control needs to be done to reduce the buildup of plaque on the surface of the teeth. Gargling with boiled water from guava leaves is one effort that is believed to be able to reduce dental plaque scores because it has antiseptic, antibacterial and antimicrobial activity. The aim of this study was to determine the effect of gargling boiled water with guava leaves on reducing plaque scores in adolescents at the Sejati Muhammadiyah Rappang Child Welfare Institution. The type of research used is experimental research using a One group pre-test post-test research design. The sample in the study was 30 people taken using purposive sampling technique. Before gargling boiled guava leaf water, the participants' average plaque score was 2.193 with moderate criteria, there was a decrease of 0.536 to 1.656 with good criteria. The data was analyzed using the Paired T-Test and obtained a result of 0.001 or p < 0.05 so that the null hypothesis was rejected and the alternative hypothesis was accepted. Based on the research results, it can be concluded that there is an effect of gargling boiled guava leaf water on reducing plaque scores in adolescents at the Sejati Muhammadiyah Rappang Child Welfare Institution.